2019
DOI: 10.17127/got/2019.17.004
|View full text |Cite
|
Sign up to set email alerts
|

The global change impacts on forest natural resources in Central Rif Mountains in northern Morocco: extensive exploration and planning perspective

Abstract: Os impactes das mudanças globais nos recursos florestais na aŕea de montanha do Rif Central em Marrocos: da exploração extensiva às perspetivas de planeamento Referência: xxx (2019). The global change impacts on forest natural resources in Central Rif Mountains in northern Morocco: extensive exploration and planning perspective. Revista de Geografia e Ordenamento do Território (GOT), n.º 17 (junho). Centro de Estudos de Geografia e Ordenamento do Território, p. 75-92, dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Due to its topographical conditions (i.e., slopes higher than 55 • ) and geological formations (shale, marl, and marl-limestone) [57][58][59], the watershed has suffered severe soil erosion and decline of forest ecosystems' resources [57] The study area belongs to the GHISS-Nekkor aquifer, which is an important source of groundwater in that region [60]. However, insufficient and poor sanitation facilities, as well as unsustainable agriculture in the study area, have resulted in deterioration of groundwater quality in this region [60,61].…”
Section: Study Areamentioning
confidence: 99%
“…Due to its topographical conditions (i.e., slopes higher than 55 • ) and geological formations (shale, marl, and marl-limestone) [57][58][59], the watershed has suffered severe soil erosion and decline of forest ecosystems' resources [57] The study area belongs to the GHISS-Nekkor aquifer, which is an important source of groundwater in that region [60]. However, insufficient and poor sanitation facilities, as well as unsustainable agriculture in the study area, have resulted in deterioration of groundwater quality in this region [60,61].…”
Section: Study Areamentioning
confidence: 99%
“…This technique was the basis of the DERRO project (El Motaki et al, 2019a). Fruit benches are contour ditches about 50 cm wide and deep, at the bottom of which fruit trees are planted (photo 1).…”
Section: The Benchesmentioning
confidence: 99%
“…The area of the cannabis is still growing up and more forests have been destroyed to spread the agriculture of cannabis (photo 7). The study we had to compare the superficies of the Oudka forest (Table III) demonstrated that in the last 30 years, the forest area of the Oudka massif has deteriorated in terms of areas and species (El Motaki et al, 2019a).…”
Section: Forest Management Assessmentmentioning
confidence: 99%